2005
DOI: 10.1088/0031-8949/71/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Stable Solutions in the Nonlinear Ship Motion

Abstract: The dynamic stability and complicated motions of a vessel in regular sea are investigated when the frequency in the pitch is nearly twice the frequency in the roll. We use the Method of Multiple Scales to determine four first-order nonlinear ordinary differential equations that govern the modulation of the amplitudes and phases when the forcing frequency is near either the pitch or the roll natural frequency. These equations are used to determine the steady-state solutions and their stability. Force-response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Later, Nayfeh and Sanchez [20] used computers to study the bifurcation analysis and basins of safe and capsize regions. El-Bassiouny's work on nonlinear models is very extensive [21][22][23][24]. In [22], the authors considered a nonlinear ship dynamics and showed the coexistence of stable solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Nayfeh and Sanchez [20] used computers to study the bifurcation analysis and basins of safe and capsize regions. El-Bassiouny's work on nonlinear models is very extensive [21][22][23][24]. In [22], the authors considered a nonlinear ship dynamics and showed the coexistence of stable solutions.…”
Section: Introductionmentioning
confidence: 99%
“…El-Bassiouny's work on nonlinear models is very extensive [21][22][23][24]. In [22], the authors considered a nonlinear ship dynamics and showed the coexistence of stable solutions. In [25], the researcher considered the 3:1 resonance in nonlinear oscillation of a shallow arch.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed technique consists of introducing a second-order controller and coupling it to the plant through a sensor and an actuator where both the feedback and control signals are cubic. El-Bassiouny [33] studied the dynamic stability and complicated motions of a vessel in regular sea are investigated when the frequency in the pitch is nearly twice the frequency in the roll. El-Bassiouny [34] investigated vibration and chaos control of nonlinear torsional vibrating systems.…”
Section: Introductionmentioning
confidence: 99%